If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x = 7x + 10 Reorder the terms: 10 + -2x = 10 + 7x Add '-10' to each side of the equation. 10 + -10 + -2x = 10 + -10 + 7x Combine like terms: 10 + -10 = 0 0 + -2x = 10 + -10 + 7x -2x = 10 + -10 + 7x Combine like terms: 10 + -10 = 0 -2x = 0 + 7x -2x = 7x Solving -2x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -2x + -7x = 7x + -7x Combine like terms: -2x + -7x = -9x -9x = 7x + -7x Combine like terms: 7x + -7x = 0 -9x = 0 Divide each side by '-9'. x = 0 Simplifying x = 0
| 24=8+v | | 6(x+2)=33 | | 90=180-x | | 3(x+2)+9x= | | -5x+8=-7-2x | | 7y-8=y+2 | | 5N+45=7N-2(N-2) | | 3n+(-50)=550 | | x/7-4=-12 | | 0=-x^2+6x+3 | | 24x^3=4x^2+4x | | (x+32)3+5(x+32)3+(x+32)+1=0 | | y=mx+bfory | | -3+10=4x+17 | | .5y=2.5+3y | | u-(-0.03)=3.2 | | 3/8=4j=1/4 | | (x^2)^6/x^8 | | 36=-8v+6(v+7) | | (6*7+x*7)+7x=9 | | 12+2x=x | | X^6-2x^2+1=0 | | 8/0.08 | | (81x^6)^(1/2) | | 3t(8)+(-2)(7c)= | | -2y=-128 | | 5x+6=6+7x | | 7x+7=105-7x | | Y^2-10y+25=8 | | 3(x-0.5)+1=3x-0.5 | | 1+7x=3x+37 | | A(x)=-2x^2+300 |